Analysis on launching of the new product of Olympic, “FrostDelight” focused on the branding and communication - Rakibuzzaman, Md. (Brac University, 2019)
This internship report is submitted in partial fulfillment of the requirements for the degree of Masters of Business Administration, 2019.